Maackiain Modulates miR-374a/GADD45A Axis to Inhibit Triple-Negative Breast Cancer Initiation and Progression - Peng, Fu; Wang, Li; Xiong, Liang; Tang, Hailin; Du, Junrong; Peng, Cheng (Frontiers in Pharmacology, 2022)
Breast cancer is the one of the most common and lethal malignancies among women worldwide, with a sharp increase of incidence since 2008. Triple negative breast cancer (TNBC) gives rise to the largest proportion in breast cancer-related death on account of its aggressive growth and rapid metastasis. Hence, searching for promising targets and innovative approaches is indispensable for the TNBC treatment. Maackiain (MA), a natural compound with multiple biological activities, could be isolated from different Chinese herbs, such as Spatholobus suberectus and Sophora flavescens. It was first time to report the anti-cancer effect of MA in TNBC. MA could suppress TNBC cell proliferation, foci formation, migration, and invasion. MA also exerted a significant inhibitory effect on tumor growth of TNBC. Furthermore, MA could induce apoptosis with an increase of GADD45α and a decrease of miR-374a. In contrast, overexpressing miR-374a would result in at least partly affecting the proapoptotic effect of MA and suppressing GADD45α stimulated by MA. These results reveal the anti-TNBC effect of MA in vitro and in vivo, providing with evidence for its potential as a drug candidate utilized in TNBC therapy.